Pemasaran Politik Pasangan Bobby Nasution Dan Aulia Rachman Pada Pilkada Medan Tahun 2020 - Mayang Sari; Muhammad Iqbal Zubaidi; Marzuki Manurung (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Democracy gives every citizen the right to be able to participate in the formulation, development, and law-making, either directly or through representatives. Democracy covers the social, economic, and cultural fields. This condition allows freedom and diversity in the practice of politics in a democratic system. The word democracy comes from the Greek “dēmokratía” which means “rule of the people,” which is formed from the words “dêmos” which means “the people” and “kratos” which means “power” or “power”. In a democratic system, there is an election mechanism known as elections (general elections), elections become a tradition or political culture in a democratic government system. A. Ubaidillah and Abdul Rozak in a book entitled Citizenship Education (Pancasila, Democracy, Human Rights, and Civil Society) explain that, Election is a system or implementation of Democracy to determine the change of position or government power, in which the people are involved in the process of electing leaders and deputy leaders in parliament, national leaders, and regional leaders. Elections are activities that involve citizens (the people) to choose leaders or representatives of the people in a democratic country. The principles in elections are direct, public, free, confidential, honest, fair and safe.